3D printed scaffolds loaded with BMP-2 for bone defect regeneration: a systematic review and meta-analysis - Li, Lei; Yang, Lishi; Yang, Yue; Zhu, Jiayi; Shi, Rongnan; Deng, Qi; Wang, Jianxiong; Sun, Fuhua (Frontiers in Physiology, 2025)
BackgroundThree-dimensional (3D) printing technology and bone morphogenetic protein- 2 (BMP-2) represent promising strategies for promoting bone regeneration.ObjectivesThis systematic review aims to assess the effects of 3D printed scaffolds loaded with BMP-2 on bone regeneration in preclinical studies.MethodsWe conducted a search in the PubMed, Web of Science, and Embase databases. Based on the inclusion and exclusion criteria, we selected and evaluated original research articles investigating on the effects of 3D printed scaffolds loaded with BMP-2 in vivo bone regeneration. The selected studies underwent bias risk assessment and sensitivity analysis. We then performed a random effects meta-analysis to evaluate the efficacy of BMP-2 loaded 3D printed scaffolds, with results presented as standardized mean differences (SMD) and their corresponding 95% confidence intervals. Subgroup analyses were conducted based on animal species, size of bone defects, and treatment duration. This review included 17 studies for meta-analysis.ResultsBMP-2 loaded 3D printed scaffolds significantly increased both the bone volume to total volume ratio (BV/TV) [2.15 (1.14, 3.16)], the percentage of new bone volume [3.07 (1.86, 4.28)], and the percentage of new bone area [3.93 (1.51, 6.35)].ConclusionPreclinical evidence substantiates the capacity of BMP-2- functionalized 3D-printed scaffolds to promote bone regeneration through spatially controlled osteoinductive signaling. These findings provide important insights for the future application of such scaffolds in bone regeneration or repair in subsequent research.